Pregabalin abuse in adolescence: a case series - Alan, Burcu Ersöz; Kızılkan, Melis Pehlivantürk; Akgül, Sinem (The Turkish Journal of Pediatrics, 2022)
Background. Pregabalin is an inhibitor of gamma-aminobutyric acid (GABA) and can be abused, especially by polydrug abuser adults. Drug abuse is one of the many risky behaviors that can be seen during adolescence. Here, three adolescents with pregabalin abuse were described. Case. These adolescents abused pregabalin to cope with their depressive and anxiety symptoms, become tranquilized, boost other drug effects, and reduce withdrawal symptoms. Therefore, the risk factors should be assessed while pregabalin is prescribed to adolescents. Conclusions. The cases were reported in order to increase awareness concerning the abuse risk of pregabalin among adolescents.
Keywords: adolescent; pregabalin; prescribed drug addiction; substance use disorder